(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Within cloud-to-things gamut, Fog is an embryonic design for storing data, performing computations, controlling applications that allocates many of such facilities to the end users. It is applicable to both wireline and mobile situations, spans software as well as hardware, sits on the edge of network as well as among end users and across access networks, and encompasses control as well as data planes. The review spots most noteworthy applications of fog computing. It supports an increasing number of applications as an architecture that includes fifth-generation (5G) wireless systems, Internet of Things (IoT), and integrated artificial intelligence (AI). The possibilities and problems of fog are summarized in this survey study, which focuses mainly on the networking environment of IoT. Fog is importance edge’s stems from the conventional cloud’s inadequacies as well as the development of new possibilities for the IoT, 5G, and embedded AI.